Association between a TGFBR2 Gene Polymorphism (rs2228048, Asn389Asn) and Acute Rejection in Korean Kidney Transplantation Recipients. (May 2013) - Kim, Yeong-Hoon; Kim, Tae Hee; Kang, Sun Woo; Kim, Hyun Ju; Park, Seok Ju; Jeong, Kyung Hwan; Kim, Su Kang; Lee, Sang Ho; Ihm, Chun Gyoo; Lee, Tae Won; Moon, Ju Young; Yoon, Young Chul; et al.
<x xml:space="preserve">Abstract</x> Transforming growth factor-β (TGF-β) signaling transduction initiates TGF-β activation, resulting in activation of TGF-β receptor II (TGFBR2). Any quantitative and qualitative changes in TGFBR2 are expected to affect the TGF-β signaling pathway, which occupies a central position with respect to the regulation of cell growth, differentiation, apoptosis, immune reaction, angiogenesis and extracellular matrix formation. Recent studies have shown that TGF-β1 gene polymorphisms may confer susceptibility to early acute and chronic allograft rejection in kidney transplantation recipients. In this study, we assessed whether polymorphisms of the TGFBR2 gene were associated with susceptibility to kidney transplantation rejection. A total of 347 renal allograft recipients transplanted at three centers in Korea were analyzed. Three SNPs (rs764522, rs3087465, rs2228048) of the TGFBR2 gene were genotyped from genomic DNA with direct sequencing. Multiple logistic regression models (codominant, dominant, recessive, and log-additive) were performed to evaluate odds ratios (ORs), 95% confidence intervals (CIs), and p-values. A total of 63 patients (18%) developed acute rejection (AR). There were no significant differences in age, sex, number of HLA mismatches, cause of renal failure, or immunosuppressant regimen between the AR and non-AR group. The synonymous SNP rs2228048 was significantly associated with AR (p = 0.020 in recessive model, and p = 0.036 in log-additive model. The allele frequencies of rs2228048 were different between the AR and non-AR group (p = 0.026). These results suggest that the synonymous TGFBR2 gene SNP rs2228048 may be associated with the development of AR in Korean kidney transplantation recipients. Authors Yeong-Hoon Kim and Tae Hee Kim contributed equally to this work and are considered co-first authors.